2017
DOI: 10.4236/jep.2017.81001
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Removal Efficiencies of <i>Chlorella vulgaris</i> from Urban Wastewater for Reduced Eutrophication

Abstract: Urban wastewater contains both organic and inorganic nutrients and discharge of untreated water increases nitrogen and phosphorous content in water bodies leading to eutrophication problem. Physical and chemical treatment of urban waste water produces large quantities of waste sludge associated with secondary pollution. Microalgae can assimilate nutrients especially nitrogen and phosphorous from wastewater for their growth and produce valuable biomass and lipid. This study was performed to determine the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 44 publications
0
22
0
3
Order By: Relevance
“…The low levels of orthophosphate compared with those found by Luo et al (2014) (~12.3 mg L -1 ) using the biofloc system, may be related to the abundance of the genera Chlorella (41-57% phytoplankton community) in all treatments. According to Ruiz et al (2011) and Singh et al (2017), C. vulgaris has a high potential for reducing the phosphorus of effluents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low levels of orthophosphate compared with those found by Luo et al (2014) (~12.3 mg L -1 ) using the biofloc system, may be related to the abundance of the genera Chlorella (41-57% phytoplankton community) in all treatments. According to Ruiz et al (2011) and Singh et al (2017), C. vulgaris has a high potential for reducing the phosphorus of effluents.…”
Section: Discussionmentioning
confidence: 99%
“…About 60% of the nitrogen and 65% of the phosphorus that enter in the system are not converted into shrimp biomass (Silva et al, 2013). An alternative used to overcome the disadvantages is the use of microalgae in this system, due to their highly efficient removal of nitrogen and phosphorus (80-100%) in aquaculture, livestock and industry as have been reported by Prajapati et al (2014), Posadas et al (2015), Kuo et al (2016) and Singh et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…El-Kassas and Mohamed (2014) reported that the microalga is used in bioremediation of aquatic environment polluted with lead (Pb), cadmium (Cd), zinc (Zn), chromium (Cr) and mercury (Hg). Chlorella vulgaris is good at utilising the excess nutrients in aquatic environment thereby reducing the eutrophication level, as they have been reported to remove about 98.4% and 87.9% of total phosphorous and total nitrogen from polluted water (Sirakov et al 2015;Singh et al 2017). Chlorella spp.…”
Section: Bioremediation Of Aquatic Environmentmentioning
confidence: 99%
“…Among the outdoor PBRs, PBR3 displayed better algal density and growth rate than the PBR4. The growth difference between PBR1 and Singh et al [20] conducted an indoor experiment with 250-ml bottles. In their experiment, maximum algal density of C. vulgaris was 1.09 g/l and productivity was 0.17 g/l/d in controlled Bold's Basal medium, whereas with wastewater and no pH control, algal density was 1.13 g/l and productivity was 0.19 g/l/d.…”
Section: Algal Growthmentioning
confidence: 99%
“…Chlorella vulgaris did not grow in PBR2; however, energy consumption and cost of PBR2 have been discussed here. Some experiments were successfully conducted in indoor cultivation without pH control, e.g., experiment conducted by [20]. As microalgae in PBR1 required 10 days to reach maximum density, 10 days time period was considered for energy and cost analysis of both PBR1 and PBR2.…”
Section: Energy Consumptionmentioning
confidence: 99%